Pengaruh Islamic Branding Terhadap Customer Loyalty Dengan Brand Awareness Sebagai Variabel Mediasi (Studi Pada Pengunjung Lafayette Coffe And Eatry, Kota Malang) - Hilda Dwi Aprilia; Noor Shodiq Askandar; Muhammad Tody Arsyianto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the influence of Islamic Brandingon Customer Loyalty, with Brand Awarenessas a mediating variable, among visitors to Lafayette Coffee and Eatry in Malang City. The study employed a quantitative approach with a survey method involving 120 respondents selected using a purposive sampling technique. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS).The results indicate that Islamic Brandinghas a positive and significant effect on Brand Awarenessand Customer Loyalty. Furthermore, Brand Awarenessalso has a positive and significant effect on Customer Loyaltyand has been shown to mediate the effect of Islamic Brandingon Customer Loyalty. These findings suggest that implementing Islamic Brandingwill be more effective in increasing Customer Loyaltyif it can first build strong Brand Awareness. This research is expected to contribute to the development of sharia marketing and serve as a practical reference for halal culinary businesses in designing sustainable branding strategies. Keywords: Islamic Branding, Brand Awareness, Customer Loyalty, Sharia Marketing, Halal Culinary Industry